Numerical investigation of subcooled boiling heat transfer in helically-coiled tube - Haryoko, L.A.F. (Universiti Malaysia Pahang, 2020)
Subcooled boiling heat transfer in helically-coiled tubes offers better heat transfer performance than any other types of boiling processes due to its ability to capture high heat flux with a relatively low wall superheat. This study investigates turbulent subcooled forced convection boiling performances of water-vapour in a helically-coiled tube with various operating conditions i.e. operating pressure, heat, and mass flux. Developed CFD model is validated against previously published experimental results using the RPI model. The model is developed based on the Eulerian-Eulerian framework coupled with k-e RNG turbulence model and Standard Wall-Function. A good agreement is found between numerical prediction and experimental counterpart for the bulk fluid temperature and non-dimensional length. The result indicates that the subcooled boiling heat transfer in a helically-coiled tube tends to improve heat transfer coefficient and pressure drop in the domain. Subcooled boiling starts at the inner side of the helically-coiled tube (f=990Â°) due to the existence of secondary flow that comes from the coil curvature. Heat transfer coefficient and pressure drop increased with increasing heat flux and decreasing mass flux, and operating pressure. This is caused by the bubble movement and convective heat transfer phenomena in a helically-coiled tube. Finally, this study can provide a guideline for future research of the subcooled boiling in a helically-coiled tube. Â© The Authors 2020.